The Implementation of the Policy on Strengthening Cultural Values and Local Wisdom in Elementary Schools - Suardin; Manan; Lisma (The Indonesian Institute of Science and Technology Research, 2025)
Technological advances in the era of globalization have caused a shift in social values, which has the potential to reduce the younger generation's understanding and appreciation of their cultural heritage. In response to this situation, the Baubau City Government has established policies, but elementary school students' awareness and understanding of preserving Buton's cultural values and local wisdom are still minimal. This study comprehensively examines the implementation of policies to strengthen cultural values and local wisdom in elementary schools in Baubau City, using a qualitative approach with a case study method. Data was obtained through observation, in-depth interviews, and documentation at three elementary schools. The data shows that the policy has been integrated into intracurricular and extracurricular activities and the creation of school culture through the instillation of discipline and school rules, with several obstacles found, including limited resources and suboptimal monitoring, evaluation, and accountability. These findings provide effective input for the formulation of policies and guidelines for the sustainable implementation of strengthening Buton’s cultural values and local wisdom.